A comparative analysis of vaccine lists, prices, and candidates, and the national immunization program between China and the United States - Xingxian Luo; Jingwen Liu; Xin Du; Jingshu Yang; Xiaomeng Jiang; Zhuangqi Li; Yifan Wu; Yue Yang (Compuscript Ltd, 2024)
Vaccines have an essential role in preventing infectious diseases and reducing the burden of disease. The differences in vaccine lists and prices, and the National Immunization Program (NIP) and vaccine development between China and the United States (US) in conjunction with epidemiologic data on infectious diseases were systematically compared. The epidemiologic data of infectious diseases in 2019 were extracted from the China National Health Commission and the US Centers for Disease Control and Prevention (CDC). The vaccine list was identified from the China National Medical Products Administration and US Food and Drug Administration databases. Vaccine prices were obtained via the China government procurement platform and the US CDC. The NIP vaccines for China and the US were obtained from the China and US CDCs. Vaccine candidates investigated in 2015-2022 were identified from the China Clinical Trial Registry Platform and the US clinicaltrials.gov database. Differences in the incidence of infectious diseases between China and the US were detected with both countries facing a lack of available vaccines for prevention of many diseases. The number of listed vaccines and preventable diseases in China was 59 and 36, respectively, which was higher than the US (45 and 31, respectively). The median price of NIP vaccines in China was significantly lower than the price in the US (median: $3.8 vs. $20; P <0.001); however, there was no significant difference in the price of non-NIP vaccines (median: $68 vs. $86; P =0.498). Vaccines developed by local manufacturers were less expensive than imported products despite the absence of significant differences (median: $16 vs. $31; P =0.180). The number and types of NIP vaccines used to prevent infectious diseases in China were lower than the US. The majority of vaccine candidates in China were not novel compared to the US. Vaccines marketed in China for infectious diseases were comparable to the US. Our findings suggest that China should further expand NIP vaccines and incentive research and development on novel vaccines to improve accessibility based on infectious disease epidemiology.